Qualidade estrutural de um latossolo vermelho cultivado com cafeeiro em função do tempo e declividades - Souza, Zélio Resende de (2019)
Brazil is known for its productive potential in agricultural areas and the coffee sector occupies a prominent place in the country's trade balance. The vast majority of coffee production areas are managed with the help of agricultural machinery and equipment that reduce production costs and increase operating yield, however they can promote serious problems when used incorrectly, which can degrade the soil structure. The knowledge of the load bearing capacity of the soil for management purposes and the application of compatible dynamic pressures, help to preserve the physical, chemical and biological properties of the soil and, contributing to the production of food in the world. Among the soil structure degradation processes, compaction has been identified as the main one. Thus, the objective of this work was to develop load-bearing capacity models of a Red Oxisol for different slope classes of the terrain usingthe uniaxial compression tests and to evaluate the agricultural machinery impact on coffee crop management at different ages. Dynamic pressure readings were also taken with a pressurometer in order to know the dynamic pressures applied by the equipment. The load-bearing capacity models were not statistically different at the age of eleven and thirteen years in the superficial layer and the age of fifteen years there was no difference between the layers. The management time did not differ statistically in terms of the impacts caused by the management on the soil structure and the K3500 harvester applied greater dynamic pressure on the soil structure.